CB2 Cannabinoid Receptor As Potential Target against Alzheimer's Disease - Aso, Ester; Ferrer, Isidro (Frontiers in Neuroscience, 2016)
The CB2 receptor is one of the components of the endogenous cannabinoid system, a complex network of signaling molecules and receptors involved in the homeostatic control of several physiological functions. Accumulated evidence suggests a role for CB2 receptors in Alzheimer's disease (AD) and indicates their potential as a therapeutic target against this neurodegenerative disease. Levels of CB2 receptors are significantly increased in post-mortem AD brains, mainly in microglia surrounding senile plaques, and their expression levels correlate with the amounts of Aβ42 and β-amyloid plaque deposition. Moreover, several studies on animal models of AD have demonstrated that specific CB2 receptor agonists, which are devoid of psychoactive effects, reduce AD-like pathology, resulting in attenuation of the inflammation associated with the disease but also modulating Aβ and tau aberrant processing, among other effects. CB2 receptor activation also improves cognitive impairment in animal models of AD. This review discusses available data regarding the role of CB2 receptors in AD and the potential usefulness of specific agonists of these receptors against AD.